Evaluation of pharmaceutical assistance in community pharmacies in COVID-19 times in the city of Belém/PA (Research, Society and Development, 2022)
Introduction: In March 2020, the world health organization announced the COVID-19 pandemic, a respiratory disease caused by the SARS-CoV-2 virus, responsible for significant impacts on health systems. During this period, community pharmacies were the first access points for some patients, making pharmaceutical assistance in this location indispensable. Objective: To evaluate the importance and benefits of pharmaceutical assistance in community pharmacies in the city of Belém/PA during the pandemic. Methods: This was a cross-sectional, quantitative and qualitative study, using an electronic form, for patients and pharmacists from community pharmacies in the city in the period of December 2021. Results: After data analysis, 67 population questionnaires and 47 of pharmacists. It was observed that several participants were diagnosed through the symptoms of the disease, the most determining being: fever (54%) and loss of smell and taste (50%). Pharmaceutical guidelines (40.3%) stand out, second only to medical advice (44.8%), which are said to be satisfactory (63.7%), and followed (62.7%). Evidencing the use of paracetamol and vitamin C (26.9%) as the most used over-the-counter medications in this period, followed by azithromycin (55%), ivermectin (48.9%) and kit-covid (40.4 %). Conclusion: In the face of emergency confrontation in public health, pharmaceutical assistance is paramount, establishing the pharmacist as the professional promoter of Health with a multidisciplinary team, requiring constant improvement, through courses or lectures so that this service to the community can continue to be developed successfully.